A Protocol for the Use of Case Reports/Studies and Case Series in Systematic Reviews for Clinical Toxicology - Nambiema, Aboubakari; Sembajwe, Grace; Lam, Juleen; Woodruff, Tracey; Mandrioli, Daniele; Chartres, Nicholas; Fadel, Marc; Le Guillou, Adrien; Valter, Remi; Deguigne, Marie; Legeay, Marion; Bruneau, Chloe; et al. (Frontiers in Medicine, 2021)
Introduction Systematic reviews are routinely used to synthesize current science and evaluate the evidential strength and quality of resulting recommendations. For specific events, such as rare acute poisonings or preliminary reports of new drugs, we posit that case reports/studies and case series (human subjects research with no control group) may provide important evidence for systematic reviews. Our aim, therefore, is to present a protocol that uses rigorous selection criteria, to distinguish high quality case reports/studies and case series for inclusion in systematic reviews. Methods This protocol will adapt the existing Navigation Guide methodology for specific inclusion of case studies. The usual procedure for systematic reviews will be followed. Case reports/studies and case series will be specified in the search strategy and included in separate sections. Data from these sources will be extracted and where possible, quantitatively synthesized. Criteria for integrating cases reports/studies and case series into the overall body of evidence are that these studies will need to be well-documented, scientifically rigorous, and follow ethical practices. The instructions and standards for evaluating risk of bias will be based on the Navigation Guide. The risk of bias, quality of evidence and the strength of recommendations will be assessed by two independent review teams that are blinded to each other. Conclusion This is a protocol specified for systematic reviews that use case reports/studies and case series to evaluate the quality of evidence and strength of recommendations in disciplines like clinical toxicology, where case reports/studies are the norm.